Study about the Modern State in Comparative Inquiry - Lane, Jan-Erik (Research Developments in Arts and Social Studies Vol. 4, 2022)
Norwegian macro-oriented Social Scientist Stein Rokkan often argued for the relevance of comparative historical inquiry. What can comparative longitudinal analyses of the state teach? The term “state” is core in politics. When do states appear on the real stage? My assessment is that F. Fukuyama’s The Origins of Political Order [1] attempts to demolish the established perspective. The separation between state and church has not been implemented in all countries. Fukuyama writes that prophet Mohammed laid the ground or foundation for an Arab state. I believe that he is incorrect.